Synthesis and Antimicrobial Activities of Some Acid Dyes - N. Wadia, Devang; M. Patel, Pravin (Asian Journal of Chemistry, 2010)
The present study was taken up to test inherent antimicrobial activity of some newly synthesized acid dyes with a view to develop protective clothing from these. All synthesized dyes were tested against common pathogens Escherichia coli, Bacillus subtilis and Bacillus cerus. All dyes were effective and showed zone of inhibition thereby indicating sufficient antimicrobial activity against all the microbes tested. Minimum inhibitory concentration was found to be varying from 5 to 40 μg. The textile material impregnated with these acid dyes, however, showed less antimicrobial activity, as uptake of these dyes in textile material is below minimum inhibitory concentration.